Digital library - Živković, Daniela (Array, 2013)
National teams of students who participated in 2012 Erasmus Intensive Program ’Library, Information and Cultural Management – Academic Summer School’ were asked to do researches on public libraries on Facebook in their countries. In the paper some of the results are presented and discussed.